Niger : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver, Modification of Performance Criteria, and Extension of the Arrangement-Staff Report; Staff Supplement; Press Release of the Executive Board Discussion; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Fifth Review Under the Poverty Reduction and Growth Facility (PRGF) for Niger. Growth prospects for 2007 are favorable, particularly because of strong agricultural production and buoyant investments. Inflation remains low. Growth prospects for the medium term have been improved by the rising price of uranium, which supports continued exploration and development of existing mines, although insecurity in the northern mining areas, if not checked, could slow the expansion. The IMF staff recommends completion of the review.